PTEN: A potential prognostic marker in virus-induced hepatocellular carcinoma - Ayesha Khalid; Tabinda Hussain; Sobia Manzoor; Muhammad Saalim; Saba Khaliq (Tumor Biology, 2017)
PTEN is the second most frequently mutated tumor suppresser gene in cancers after p53. Genetic and epigenetic alterations in the PTEN gene and its regulatory regions have been reported in various studies. PTEN is a crucial downregulator of the pro-survival phosphoinositide 3-kinase/Akt/mammalian target of rapamycin pathway and also suppresses insulin signaling. Failure to regulate these pathways leads to increase in cell proliferation and migration which in turn promotes tumorigenesis. PTEN underexpression is mediated by a variety of cytokines and stress kinases which seem to collectively induce the RAS/mitogen-activated protein kinase (MAPK)/extracellular signal–regulated kinase (ERK) pathway. In the context of hepatocellular carcinoma, reduced expression of PTEN is seen in nearly half of the cases on average. In some cases, PTEN has been observed to be either mutated or methylated which can also lead to reduced expression or in some cases, complete loss of expression. On the cellular level, PTEN is also a target in the pathogenic pathway of hepatitis C virus core protein and hepatitis B virus X protein. These viruses appear to alter PTEN regulation and pro-apoptotic ability to enhance the process of tumor formation. In perspective of the crucial role PTEN plays in balancing proliferation and apoptosis, we propose PTEN as a valuable marker in the diagnosis, assessment of tumor grade, and disease stage in hepatocellular carcinoma patients.